2010
DOI: 10.5194/acpd-10-2245-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of West African Monsoon convective transport and lightning NO<sub>x</sub> production upon the upper tropospheric composition: a multi-model study

Abstract: Abstract. Within the African Monsoon Multidisciplinary Analysis (AMMA), we investigate the impact of nitrogen oxides produced by lightning (LiNOx) and convective transport during the West African Monsoon (WAM) upon the composition of the upper troposphere (UT) in the tropics. For this purpose, we have performed simulations with 4 state-of-the-art chemistry transport models involved within AMMA, namely MOCAGE, TM4, LMDz-INCA and p-TOMCAT. The model intercomparison is complemented with an evaluation of the simul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
2
10
0
Order By: Relevance
“…(c) Above 500 hPa, the ozone mixing ratios rapidly increased with a range of 60 to nearly 100 ppb in the 400-300 hPa layer which is most likely linked to production of LNO X over West Africa and transported westward towards Cape Verde. The production of LNO X leading to an increase in downstream O 3 mixing ratios over the tropical Atlantic is consistent with Global Chemical Transport Model (GCTM) results [Barret et al, 2010].…”
Section: Discussionsupporting
confidence: 87%
“…(c) Above 500 hPa, the ozone mixing ratios rapidly increased with a range of 60 to nearly 100 ppb in the 400-300 hPa layer which is most likely linked to production of LNO X over West Africa and transported westward towards Cape Verde. The production of LNO X leading to an increase in downstream O 3 mixing ratios over the tropical Atlantic is consistent with Global Chemical Transport Model (GCTM) results [Barret et al, 2010].…”
Section: Discussionsupporting
confidence: 87%
“…missed fires, cloud cover that can mask the detection of fires under the cloud fields, all causing underestimation of the emissions (Pereira et al, 2009). In fact, other studies reported that GFED2 inventory might underestimate CO emissions (van der Werf et al, 2006;Jones et al, 2009;Turquety et al, 2009;Barret et al, 2010). Recent versions of the model from v-01-02 and later accept GFED3 updated inventory, which might have solved this issue.…”
Section: Integration Of Geos-chem Model Results With Previous Analysesmentioning
confidence: 99%
“…This run used the boundary layer mixing scheme of of Holtslag and Boville (1993), and is therefore very similar to run TOMCAT R2. In pTOMCAT-tropical, the original implementation of the convective scheme used in p-TOMCAT has been updated to increase convective transport to the mid and upper troposphere (Barret et al, 2010). The entrainment rate is set to be half the value suggested by Tiedtke (1989).…”
Section: Ptomcat Ctmmentioning
confidence: 99%